(untitled) (Albany, 1993)
This book brings together the best writing on Japanese business in a comprehensive reader, illustrating the impact of Japanese culture and lifeways on all facets of business behavior. The authors examine not only Japanese management, but also production, accounting, marketing, distribution, law, and interpersonal relationships. Essays include analyses by businessmen, management scholars, anthropologists, and lawyers, all in one accessible volume for those concerned with Japanese business performance, the international business climate, and cooperative ventures between cultures and corporations.
Keywords: Industrial management,Corporate culture,Quản lí công nghiệp,Văn hóa doanh nghiệp; Japan,Japan,Nhật Bản,Nhật Bản